(untitled) (Modern education and development, 2024)
In the modern globalized world, foreign language proficiency is a critical skill for university students, equipping them for academic, professional, and personal success. This article examines the specific features of teaching foreign languages to university students in contemporary conditions, emphasizing the relevance of multilingualism, the integration of innovative teaching methodologies, and the importance of practical training. It highlights the cognitive, cultural, and professional advantages of multilingualism and discusses the use of technology, intercultural competence, and international exchange programs in language education. The article also addresses the challenges of language instruction, such as resource limitations and student motivation, offering strategies to overcome these barriers. By fostering linguistic and cultural fluency, universities can prepare globally competent graduates capable of navigating diverse professional landscapes and contributing to international collaboration.